Systematic Review of Factors Affecting Economic Growth from the Tourism Aspect - Zaim Mukaffi; Tri Haryanto (PROGRAM STUDI PARIWISATA SYARAH, FAKULTAS EKONOMI DAN BISNIS ISLAM, UNIVERSITAS ISLAM NEGERI MATARAM, 2022)
Purpose: The purpose of this systematic review is to identify the factors that influence regional and national economic growth in terms of tourism demand. Method: In the three rounds of analysis used in this review, descriptive approaches rather than statistical ones are restricted in terms of methodology. For the data, 40 journals were used. Result: The findings of this systematic review indicate that the number of tourist visits, income, networks, and attractions, as well as the amount of government spending on the tourism industry, capital investments, the number of workers, the number of restaurants/restaurants, and the availability of hotel rooms, are all factors that have an impact on economic growth and the caliber of the infrastructure. Contribution: This article offers a thorough analysis of the variables affecting the key economic growth from the tourist sector.